1998
DOI: 10.1161/01.hyp.32.2.360
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Tone and Arterial Wall Viscosity

Abstract: Abstract-The relationships between steady and pulsatile pressures, smooth muscle tone, and arterial viscoelastic behavior remain a matter of controversy. We previously showed that arterial wall viscosity (AWV) was 3-fold lower in vivo than in vitro and suggested that in vivo active mechanisms could minimize intrinsic AWV to improve the efficiency of heart-vessel coupling energy balance. The aim of the present study was to determine the role of smooth muscle tone on AWV, under various levels of steady and pulsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 25 publications
5
48
0
Order By: Relevance
“…They concluded that urethral stress relaxation was significantly greater in SUI than for healthy females, with the greatest differences occurring at the bladder neck or proximal urethral segment. The viscoelasticity of muscular tissues is related to the basal tone of the tissue (2,8,32). Therefore, our observation that VD leads to a decrease in basal tone in the urethra is consistent with the finding by Thind and Lose (38) that urethral viscoelasticity is altered in SUI.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They concluded that urethral stress relaxation was significantly greater in SUI than for healthy females, with the greatest differences occurring at the bladder neck or proximal urethral segment. The viscoelasticity of muscular tissues is related to the basal tone of the tissue (2,8,32). Therefore, our observation that VD leads to a decrease in basal tone in the urethra is consistent with the finding by Thind and Lose (38) that urethral viscoelasticity is altered in SUI.…”
Section: Discussionsupporting
confidence: 92%
“…Due to the nonuniform nature of the urethra along its length (10), a thickness must be determined for each segment (i.e., proximal, middle, and distal segments) separately to calculate R i from the measured Ro for use in Eqs. [1][2][3][4][5]. Thus, after the biomechanical ex vivo testing was performed, specimens were fixed under zero transmural pressure in 4% paraformaldehyde overnight, followed by 30% sucrose solution.…”
Section: Animalsmentioning
confidence: 99%
“…Indeed, the structural bases for the static and dynamic mechanical properties of the vascular wall have been extensively studied both in in vitro experiments [2] and in in vivo experimental animals [3]. Furthermore, the influence of the specific constituents of the arterial wall on the mechanical properties of the vessel has been investigated, focusing the analyses on determining their role in the elasticity of arteries [4].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, however, BAUER et al [28] reported that, in contrast with the static modulus, the dynamic elastic modulus and the coefficient of wall viscosity were virtually uninfluenced by smooth muscle tone, when various arterial segments were studied in vitro under the condition of activation induced by noradrenalin and relaxation induced by papaverine. BOUTOUYRIE et al [30] confirmed in vivo that wall viscosity was not influenced by smooth muscle tone. The above observations were made on systemic arteries, and it remains to be established whether pulmonary arteries behave in a similar fashion.…”
Section: Effect Of Cardiac Pathologymentioning
confidence: 93%
“…wall viscosity. Recently, however, it was shown that sustained changes in smooth muscle tone did not influence aortic wall viscosity [30].…”
Section: Effect Of Exercisementioning
confidence: 99%